Analisis Faktor-Faktor Yang Memengaruhi Kinerja Sistem Informasi Akuntansi Pada Bank Perkreditan Rakyat (BPR) di Kota Denpasar - Mahardika, Ida Bagus Gede Agastya; Suardhika, I Made Sadha (E-Jurnal Akuntansi; Vol 24 No 3 (2018), 2018)
This study aims to determine the influence of user involvement in the development of information systems, the ability of personal techniques users of information systems, top management support, formalization of information systems development, training and education programs, the existence of the information system board of directors, and the location of the department of the system on the performance of accounting information systems as measured by user satisfaction of the system. The population in this research is 13 Rural Banks in Denpasar City. The sample was determined by purposive sampling method, and got 76 employees as the respondents. Data were collected by questionnaire method. The analysis technique used is multiple linear regression analysis. Based on the analysis of 76 respondents it is known that the seven variables have positive and significant effect on the performance of accounting information system at BPR in Denpasar City. Keywords: Information Technology, Accounting Information System, Rural Bank